Unexpected Findings in a Child with Atypical Hemolytic Uremic Syndrome: An Example of How Genomics Is Changing the Clinical Diagnostic Paradigm - Seaby, Eleanor G.; Gilbert, Rodney D.; Andreoletti, Gaia; Pengelly, Reuben J.; Mercer, Catherine; Hunt, David; Ennis, Sarah (Frontiers in Pediatrics, 2017)
CBL is a tumour suppressor gene on chromosome 11 encoding a multivalent adaptor protein with E3 ubiquitin ligase activity. Germline CBL mutations are dominant, with pathogenic de novo mutations reported that can phenotypically overlap Noonan syndrome.1 Some patients with CBL mutations go on to develop juvenile myelomonocytic leukaemia (JMML), an aggressive malignancy that usually necessitates bone marrow transplantation. Using whole exome sequencing methods, we identified a known mutation in CBL in a 4-year-old Caucasian boy with atypical haemolytic uraemic syndrome (aHUS), moyamoya phenomenon and dysmorphology consistent with a mild Noonan-like phenotype. Exome data revealed loss of heterozygosity across chromosome 11q consistent with JMML but in the absence of clinical leukaemia. Our finding challenges conventional clinical diagnostics since we have identified a pathogenic variant in the CBL gene previously only ascertained in children presenting with leukaemia. The increasing affordability of expansive sequencing is likely to increase the scope of clinical profiles observed for previously identified pathogenic variants and calls into question the interpretability and indications for clinical management.